An Integrated perspective of Indigenous territories in Ten Canoes - Frey, Aline (Desenvolvimento e Meio Ambiente, 2019)
Indigenous knowledge can challenge liberal and anthropocentric definitions of water as human property. In this article, I examine the close relationship of Indigenous people with their waterscapes as portrayed in the Australian feature film Ten Canoes.